Aplikasi Tipologi Kepribadian Berbasis Web untuk Efektivitas Komunikasi - Medhanita Dewi Renanti; Anggia Chrisanti Darmawan (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Communication is the process of sending and receiving messages that involve at least two people so that the message can be understood. The existence of effective communication results in a good relationship between the sender and recipient of the message. Meanwhile, miscommunication can lead to relationship breakdown. The way a person communicates is largely influenced by his personality. Communication is more effective by looking at his personality. Personality directly affects interpersonal communication and this communication affects organizational commitment. One way to find out a person's personality typology is to fill in personality observations based on the fields that have been determined by the expert. The purpose of this study is to develop a personality typology application that can be used to identify a person's personality typology. The existence of this application is expected to help realizing effective communication because someone knows the typology of his personality that can be used to communicate with his interlocutors. The software development method used is eXtreme Programming. This method was chosen because the resources to make the system were available, application development time was short, and programming was done by a small team. The making of this personality typology application can be used by someone to identify personality typologies that can produce choleric, sanguine, melancholic, and phlegmatic classification outputs. This application is created using the PHP programming language and MySQL Database Management System by displaying a list of 24 questions that must be filled in by the user. The application using black box testing, accuracy value is 100%. The existence of this application is expected to create a comfortable working atmosphere and create smooth communication with all parties. This has an impact on the effectiveness of communication so that it can reduce communication misunderstandings.